The discrepancy between manual and computerized leukocyte and thrombocyte counts - Bambang Permono; Retno Asih; I Dewa Gede Ugrasena (Indonesian Pediatric Society Publishing House, 2016)
Background Discrepancy between results of leukocyte and throm- bocyte count by computerized and manual examination may exist Objective To determine the discrepancy between computerized and manual leukocyte and thrombocyte count. Methods The design was a randomized sampling cross sectional study. The blood sample was examined with computerized Cell Dyn 1400 instrument for the leukocyte and thrombocyte count. For manual examination, blood smear was performed to measure thrombocyte while leukocyte was measured in Improved Neubauer hemocytometer. The results of computerized examination were used as gold standard. Sensitivity, specificity, predictive values of manual count were calculated. The agreement of Kappa and Mc Nemar test were determined Results Blood specimens drawn from 100 patients with different kinds of diagnoses were examined using computerized and manual methods. In computerized group, 66% had normal leukocyte and 55% had normal thrombocyte count. In the manual group, 78% of subjects had normal leukocyte and 82% had normal thrombocyte count. From leukocyte examination, the sensitivity of manual count was 87.9%, specificity was 41.2%, and positive predictive value was 74.36 with the agreement of Kappa of 0.32 and Mc Nemar value of 0.036. From thrombocyte examination, the sensitivity was 96.4%, specificity was 35.6%, and positive predictive value was 64.6 with the agreement of Kappa of 0.41 and Mc Nemar value of 0.41. Conclusion The result of manual thrombocyte count was in ac- cordance with computerized with the agreement of Kappa of 0.41. On the other hand, there was a discrepancy between manual in favor of computerized leukocyte count with the agreement of Kappa of 0.32